New sulfa drug derivatives and their zinc(II) complexes: synthesis, spectroscopic properties and in vitro cytotoxic activities - Sahal, Hakan; Oz, Samet; Keskin, Tuba; Tekin, Suat; Canpolat, Erdal; Kaya, Mehmet (Taylor & Francis Inc, 2024)
Synthesis of four sulfa drug derivatives (L-1-L-4) and Zn(II) complexes derived from sulfonamide group antibiotic substances was carried out using the hydrothermal technique (HT) and their structures of the obtained compounds were explained using elemental analysis (EA), FT-IR and NMR (H-1- and C-13-). Cytotoxic activities of four novel sulfa drug based-Schiff base compounds and their Zn(II) complexes were determined by 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyl-2H-tetrazolium bromide (MTT) assay using MCF-7 (human breast cancer), Caco-2 (human colorectal adenocarcinoma), A2780 (human ovarian cancer) and LNCaP (human prostate adenocarcinoma) cell lines. LogIC50 values of all obtained compounds were computed with the Graphpad Prism 6 program after 24 h of treatment for MCF-7, Caco-2, A2780 and LNCaP cells. Comet assay experiments were performed using LogIC(50) concentrations of all compounds to determine DNA damage. Based on the data obtained, all compounds significantly decreased MCF-7, Caco-2, A2780 and LNCaP cell viability compared to the control groups (p < 0.05). Communicated by Ramaswamy H. Sarma
Keywords: Sulfonamide antibiotics; Schiff base; Zn(II) complex; cancer cell lines; cytotoxic activity